Multi‐carrier and multi‐polarimetric model based adaptive target detector for passive radar systems. Issue 8 (16th April 2021) - Filippini, Francesca; Colone, Fabiola
Abstract: A new adaptive detection strategy for passive radar systems that fruitfully capitalizes on signals, simultaneously emitted by the same transmitter of opportunity at different carrier frequencies and collected by a set of differently polarized surveillance antennas is derived. Based on recent results that demonstrated the benefits provided by proper strategies to exploit polarimetric diversity, the authors aim at further improving the target detection performance by combining polarimetric and frequency diversity. Real data collected through an FM radio‐based passive radar prototype is used to extensively demonstrate the effectiveness of the derived strategy with respect to state‐of‐the‐art approaches. The conceived solution is proved to successfully enhance the capability to discriminate targets, thanks to an effective disturbance rejection performed at each frequency channel as well as a target echo enhancement and an increased robustness to the time‐varying characteristics of the exploited source of opportunity.